2016
DOI: 10.14474/ptrs.2016.5.1.34
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hip abductor fatigue on static balance and gait parameters

Abstract: Objective: Hip abductors play a role in providing stability and movement to the lower limbs. The purpose of this study was to examine the effects of hip abductor fatigue on static balance and gait in the general population. Design: One group pre-test post-test design. Methods: Thirteen university students in their twenties volunteered for the study and had underwent a functional assessment. To induce fatigue, the subjects were instructed to raise their dominant lower extremity up against a load of 50% of 1 rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Previous studies have shown a significant increase in gait parameters, such as the single support time, stride time variability and step-to-step asymmetry in the frontal plane, as well as significantly slower mediolateral trunk movement in fatigued leg late stance toward the non-fatigued leg during fatiguing gait [19,20]. However, these changes have been observed only after locally fatiguing the abductor muscles of the hip [19,20]. Failure to find differences in the present study between the limbs in gait parameters may be due to the reorganization of multi-joint coordination and the redistribution of active muscle activity in such a way as to compensate for muscle dysfunction caused by muscle fatigue [53].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies have shown a significant increase in gait parameters, such as the single support time, stride time variability and step-to-step asymmetry in the frontal plane, as well as significantly slower mediolateral trunk movement in fatigued leg late stance toward the non-fatigued leg during fatiguing gait [19,20]. However, these changes have been observed only after locally fatiguing the abductor muscles of the hip [19,20]. Failure to find differences in the present study between the limbs in gait parameters may be due to the reorganization of multi-joint coordination and the redistribution of active muscle activity in such a way as to compensate for muscle dysfunction caused by muscle fatigue [53].…”
Section: Discussionmentioning
confidence: 94%
“…Finally, the inter-limb differences for both spatio-temporal and strength-related parameters recorded during the support-phase-of-gait were not significant following performance of the UCVJ fatigue protocol. Previous studies have shown a significant increase in gait parameters, such as the single support time, stride time variability and step-to-step asymmetry in the frontal plane, as well as significantly slower mediolateral trunk movement in fatigued leg late stance toward the non-fatigued leg during fatiguing gait [19,20]. However, these changes have been observed only after locally fatiguing the abductor muscles of the hip [19,20].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The whole process took less than 5 minutes. If the subjects moved their arms to maintain balance, swayed in any side more than 10 degrees, or took their hands off their chest, opposite leg touched the ground, the measurement was performed again [14].…”
Section: Static Balance Measurementsmentioning
confidence: 99%